ANALYZING EXPRESSIVE SPEECH ACTS OF THE MAIN CHARACTER IN THE JOKER MOVIE - Shevira Selsibilla; Novitri Novitri; Erni Erni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This research aimed to find out the types of expressive speech acts and the context of the expressive speech acts uttered by the main character in the Joker movie. The design of the research was descriptive qualitative research. The data source was the Joker Movie directed by Todd Phillips. The movie was released in 2019 and its duration was about 1 hour 55 minutes. The data of this research were utterances included as expressive speech acts. The data were collected by watching, observing, and writing down the utterances indicated as expressive speech acts found in the movie. The data were analyzed by using formal and informal methods. The data were presented by using a table (Formal method) and description (Informal method). The contexts of the utterances were analyzed by using SPEAKING model. The results of the analysis showed that there were six classifications of expressive speech acts uttered by the main character in the Joker Movie. The total number of expressive speech acts found in the movie was 27 utterances covering 7 utterances of greeting, 6 utterances of agreeing, 5 utterances of thanking, 4 utterances of apologizing, 3 utterances of wishing, and 2 utterances of exclamation. The researcher found that the expressive speech act of greeting was the most frequently used by the main character. It showed that the main character liked to express his salutation when he met someone.